Appreciative Inquiry Training to Improve Career Maturity as a Working Capital in Students - Anggun Resdasari Prasetyo; Darosy Endah H; Lusi Ardhiani (Journal of Educational, Health and Community Psychology, 2020)
Career maturity is defined as the ability to complete career development stage. Career maturity requires appropriate intervention, one of which is Appreciative Inquiry. Appreciative inquiry is a intervention that aims to explore positive individual experiences for work readiness. This study aims to determine the effect of Appreciative Inquiry training on student career maturity. The subject of the research was 54 students of the 2017 class year at the Faculty of Psychology Undip, divided into two group (experiment and control) by random assignment. Measurement data using career maturity scale and analyzed by Mann U Whitney test. The results on the posttest data between the experimental and the control group showed a significant difference (Z= -2,385; p=0,017; p<0,05). The experimental group had a higher result (M=176.19;SD=16.52) than the control group (M=167.15;SD=5,383). This explains that the Appreciative Inquiry training can be used to improve career maturity in students.